Kajian Medis dan Etika Kontroversi Pemanfaatan Ganja di Indonesia: Tinjauan Pustaka - Dewi, Ervin Dyah Ayu Masita; Marzuki H. Y, Jefman Efendi; Mulyono, Rico (Fakultas Kedokteran Universitas Trisakti, 2023)
The use of marijuana/cannabis for therapy, especially for certain neurological diseases, is still causing controversy in various countries, including Indonesia. Various studies continue to be carried out while certain parties feel they have the right to get treatment through marijuana based on testimonials and previous research. The urge to legalize the use of marijuana as an alternative therapy is getting tougher, including in Indonesia. Judging from medical ethics, therapy can be applied if its use is following medical indications, the benefits outweigh the risks, its use respects human dignity, and has been clinically tested with scientific research. This research used literature studies from various references to analyze the medical and ethical aspects of using marijuana as a therapy. Potentially Cannabidiol in cannabis can be an alternative therapy, provided that it has passed the correct and ethical scientific research, which is not yet complete. Thus, the legalization of the use of cannabis/marijuana as a therapy still requires stronger and more valid scientific evidence so that the use of cannabis does not reduce human dignity, especially patients as vulnerable people under the pretext of humanity.